[RETRACTED ARTICLE] Pedagogical Knowledge for Technology-Enhanced Learning : A Literature Review - Lamtara, Sana (Journal of Pedagogy and Education Science, 2024)
The inexorable growth of technological use amidst COVID-19 strengthens the emerging paradigm in education and accelerates the need for technology-supported pedagogical knowledge. This paper examines how the principles of the four learning theories, behaviourism, cognitivism, constructivism, and connectivism, are implemented in the technology-enhanced learning environment to help faculty align their pedagogy and teaching methods with technology. A review is conducted to survey relevant literature concerning learning theories and pedagogical models to achieve this goal. This review relies on four major bibliographic databases: Science Direct, Scopus, Web of Science, and Google Scholar, through which many articles are identified. Twenty-seven articles are selected according to the scope of the study. Then, a qualitative analysis is conducted to determine the four learning theories implemented in the online environment. The proposed pedagogical framework classifies the four learning theories in a hierarchical hierarchy according to their adherence to the student-centred learning approach. Connectivism is at the top of the pyramid due to its vast opportunities for learners’ autonomy, interactivity, and diversity. Constructivism precedes as it is also centred on learners, allowing for knowledge construction.   RETRACTION NOTICE: This article has been formally retracted as of March 12, 2024, at the authors' request. The authors assert that a paper similar to this article1 has been published in the International Journal of Higher Education Pedagogies  (IJHEP) without their knowledge or consent. The authors maintain that, having previously submitted their work to IJHEP for review before submitting it to JPES, they received no communication from IJHEP regarding the publication status, leading them to believe that their submission had been disregarded. Operating in good faith under this assumption, the authors subsequently submitted their article to JPES. In their statement, the authors emphasize that they never intended for their paper to be concurrently published in two journals, as they fully comprehend the ethical implications associated with such actions. 1https://www.diamondopen.com/journals/index.php/ijhep/article/view/412